2011
DOI: 10.1177/0145445511415396
|View full text |Cite
|
Sign up to set email alerts
|

Detecting False Positives in Multielement Designs

Abstract: The authors assessed the extent to which multielement designs produced false positives using continuous duration recording (CDR) and interval recording with 10-s and 1-min interval sizes. Specifically, they created 6,000 graphs with multielement designs that varied in the number of data paths, and the number of data points per data path, using a random number generator. In Experiment 1, the authors visually analyzed the graphs for the occurrence of false positives. Results indicated that graphs depicting only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 19 publications
1
33
0
2
Order By: Relevance
“…The results of this study extended findings from the Bartlett et al (2011) study on false positive with multielement designs and provide support for the objectivity of behavior changes detected in A-B designs. In addition, the results of this study potentially strengthen the validity of nonconcurrent multiple baseline designs, which were initially introduced by Watson and Workman (1981) as an experimental design for applied researchers.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The results of this study extended findings from the Bartlett et al (2011) study on false positive with multielement designs and provide support for the objectivity of behavior changes detected in A-B designs. In addition, the results of this study potentially strengthen the validity of nonconcurrent multiple baseline designs, which were initially introduced by Watson and Workman (1981) as an experimental design for applied researchers.…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, other researchers have noted that the more immediate the change in the behavior following the introduction of the independent variable, the more likely the change will be attributed to the independent variable (e.g., Horner et al, 2012). Moreover, Bartlett et al (2011) found that the probability of producing false positives in multielement designs decreased with additional sessions. Thus, additional sessions in each phase of an A-B design would likely yield comparable or lower percentages of false positives.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations